Secure relay node selection method based on Q-learning for fog computing in 5G network - Shanshan TU; Jinliang YU; Yuan MENG; M WWAQAS; Lei LIU (Dianxin kexue)
A Q-learning-based optimal dual-relay node selection method was proposed. Firstly, a security fog computing structure model based on social awareness was constructed, and then an optimal dual-relay node selection method based on Q-learning algorithm was designed under this model, which achieved the selection of optimal dual-relay nodes in dynamic environment. Finally, the key generation rate, the selection speed of dual-relay nodes and the selection accuracy of dual-relay nodes in dynamic environment were analyzed. The experimental results show that the scheme can effectively select the optimal dual-relay nodes in dynamic environment, the algorithm converges rapidly to a stable level, and the selection speed of the optimal relay node is effectively improved.